Risk Management for 4-H Youth Development Work: Crisis Management and Emergency Procedures - Paula Davis; Dale Pracht; Stefanie Prevatt; Janet Psikogios (EDIS)
This 2-page publication is one in the series Risk Management for 4-H Youth Development Work. It focuses on basic overall precautions to be taken by everyone involved with 4-H. Written by Paula Davis, Dale Pracht, Stefanie Prevatt, and Janet Psikogios and published by the UF/IFAS 4-H Youth Development Department, February 2018. http://edis.ifas.ufl.edu/4h385